Witness protection - (:unkn) unknown (My University, 2016)
As you may know, Europol’s mission is to improve the effectiveness of theEuropean Union’s law enforcement action against organised crime, withspecial emphasis on targeting criminal organisations. Therefore, sinceEuropol took up its activities fully, in July 1999, it has been our beliefthat witness protection should be made available in all the MemberStates of the European Union, as it is a very powerful tool, if not “the”tool, in the fight against organised crime and terrorism. Presentation made at the The 10th annual Conference and General Meeting of the International Association of Prosecutors held in Copenhagen, Denmark on August 28 to September 1, 2005.